2004
DOI: 10.1086/421940
|View full text |Cite
|
Sign up to set email alerts
|

The Burst and Transient Source Experiment (BATSE) Earth Occultation Catalog of Low‐Energy Gamma‐Ray Sources

Abstract: The Burst and Transient Source Experiment (BATSE), aboard the Compton Gamma Ray Observatory (CGRO), provided a record of the low-energy gamma-ray sky ($20-1000 keV) between 1991 April and 2000 May (9.1 yr).BATSE monitored the high-energy sky using the Earth occultation technique (EOT) for point sources whose emission extended for times on the order of the CGRO orbital period ($92 min) or greater. Using the EOT to extract flux information, a catalog of sources using data from the BATSE Large Area Detectors has … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
54
2

Year Published

2005
2005
2014
2014

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 57 publications
(57 citation statements)
references
References 118 publications
1
54
2
Order By: Relevance
“…Durant et al (2011) discovered a large-scale extended component in X-rays up to 1 from LS 5039. The system has also been detected by INTEGRAL up to 200 keV (Goldoni et al 2007;Hoffmann et al 2009), and with BATSE up to 1 MeV (Harmon et al 2004). LS 5039 was first associated with an EGRET source in Paredes et al (2000), and variability was detected by Fermi between 100 and 300 GeV with a 3.9-d period (Abdo et al 2009).…”
Section: The Gamma-ray Binary Ls 5039mentioning
confidence: 99%
“…Durant et al (2011) discovered a large-scale extended component in X-rays up to 1 from LS 5039. The system has also been detected by INTEGRAL up to 200 keV (Goldoni et al 2007;Hoffmann et al 2009), and with BATSE up to 1 MeV (Harmon et al 2004). LS 5039 was first associated with an EGRET source in Paredes et al (2000), and variability was detected by Fermi between 100 and 300 GeV with a 3.9-d period (Abdo et al 2009).…”
Section: The Gamma-ray Binary Ls 5039mentioning
confidence: 99%
“…We investigated the CGRO/BATSE occultation measurements (see, e.g., Harmon et al 2004) in the period April 1991 and November 2000; they show 10-day average 20−100 keV fluxes from non-detections (with typical 10-day 3σ upper limits between about 50−70 mCrab) up to about 150 mCrab. During the period of the EURECA/WATCH observations when 4U 0614+091 was in the field of view, the 20−100 keV flux was on average 57 ± 6 mCrab; close to the time of the bursts seen by EURECA/WATCH it was around 100 mCrab.…”
Section: Asm Long-term Persistent Flux and Burst Recurrence Timesmentioning
confidence: 99%
“…However, with the only exception being the CGRO/BATSE instrument, detecting only a handful of AGN (Harmon et al 2004), long-term hard X-ray monitoring has not been possible until recent years, because of the observing strategy of the hard X-ray satellites and the limited size of the field of view of their instruments. Furthermore, latest generation and future hard-X-ray telescopes such as NuSTAR will have small fields of view and relatively inflexible scheduling capabilities, so future studies may tend to be limited to either short time scales or in the number of observed objects.…”
Section: Introductionmentioning
confidence: 99%